PERSEPSI KUALITAS, RESIKO DAN NILAI PADA KEPUTUSAN PEMBELIAN PRODUK (STUDI KASUS PRODUK TUPPERWARE PT BUMI PADANG GEMPITA) - Kevin Andeska Putra; Lola Fitria Sari; Willy Nofranita (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
This study aims to determine: 1. To determine the effect of perceived quality on purchasing decisions for Tupperware products at PT. Padang Gempita Earth; 2. To determine the effect of perceived risk on purchasing decisions for Tupperware products at PT. Padang Gempita Earth; 3. To determine the effect of perceived value on purchasing decisions for Tupperware products at PT. Desert Earth. The method used in this research is a quantitative method with a descriptive approach. The sample in this study was 120 respondents with a sampling technique using a minimum sample size according to Hair. The data analysis technique used is the structural equation modeling (SEM) method. Data analysis techniques started with conceptual models based on theory, making path diagrams, model specifications, model identification, parameter estimation, model fit assessment, model modification, and model cross-validation. This study shows the results: 1) Perceived quality has no significant effect on the decision to purchase Tupperware products at PT. Padang Gempita Earth; 2) Perceived risk has a positive effect on purchasing decisions for Tupperware products at PT. Padang Gempita Earth; 3) Perceived value has a positive and significant effect on the decision to purchase Tupperware products at PT. Desert Earth.Keywords: Perceived quality, perceived risk, perceived value, purchasing decisions